Exploring the impact of technology on traditional Chinese medicine in the RCEP framework: innovation, sustainability, and economic growth - Chen, Chanting; Huang, Xiaoxiao; Zhou, Xiangcheng (Psychology, health & medicine, 2025)
The Regional Comprehensive Economic Partnership (RCEP) brings together Asia-Pacific nations to enhance economic ties. Traditional Chinese Medicine (TCM) faces changes due to Technological Innovation (TI), presenting economic opportunities and challenges for member states. This study explored the impacts of technology on TCM production and exportation within the RCEP framework. A purposive sampling technique is used in this study to choose the samples for data collection. Utilizing a mixed method approach, valid responses were gathered from 450 participants. The collected data were subjected to analysis using the Statistical Package for the Social Sciences (SPSS) software. The study revealed that TI in TCM production indeed has significant positive implications for RCEP member states. The study found that the adoption of advanced technology in TCM production promotes innovation and sustainability within the industry, driving long-term growth for RCEP member states. The study highlights the potential for RCEP member states to leverage their collective expertise and resources to establish themselves as leaders in the global TCM industry, creating new avenues for economic development and cooperation. The study's contribution lies in highlighting how technology in TCM production can boost economic resilience and competitiveness within the RCEP framework, emphasizing its role in fostering collaboration and knowledge-sharing among member states.